1998
DOI: 10.1037/0021-843x.107.4.676
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of posttraumatic stress disorder in veterans with and without spinal cord injury.

Abstract: The authors assessed effects of paraplegic and quadriplegic spinal cord injuries (SCIs) on posttraumatic stress disorder (PTSD) by comparing severity and prevalence of PTSD in these groups to a sample of controls who experienced traumatic injuries other than SCI. The authors found that veterans with quadriplegia reported significantly less severe current PTSD symptoms than controls who were not significantly different from veterans with paraplegia. These results suggest that sustaining a quadriplegic SCI decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
65
3
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 9 publications
6
65
3
2
Order By: Relevance
“…11 The present study however did not find a significant relation between prevalence of PTSD and time since lesion. On the other hand, the time span is very small in the present study compared with the study by Radnitz et al 25 The patients in the present study ranged from 20 days to almost 1 year since the time of lesion. During this time, the patients experienced a number of secondary events, including (i) severe lesion to the spinal cord, (ii) hospitalization and in some cases transfer to another hospital to undergo surgery, and (iii) transfer to a rehabilitation centre.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…11 The present study however did not find a significant relation between prevalence of PTSD and time since lesion. On the other hand, the time span is very small in the present study compared with the study by Radnitz et al 25 The patients in the present study ranged from 20 days to almost 1 year since the time of lesion. During this time, the patients experienced a number of secondary events, including (i) severe lesion to the spinal cord, (ii) hospitalization and in some cases transfer to another hospital to undergo surgery, and (iii) transfer to a rehabilitation centre.…”
Section: Discussioncontrasting
confidence: 75%
“…11 Also, compared with a study of adult veterans with SCL, the prevalence rate in the present study is relatively high. Radnitz et al 7,8,25 found that 11.9% of 126 male veterans with SCL met the diagnosis for current PTSD, an average of 18.8 years following lesion. Based on a survival analysis, Kessler et al 11 found that two-thirds of their sample who had experienced onset of PTSD succeeded to remit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifty per cent of a sample questioned after experiencing a medical accident received high distress scores on the intrusion subscale of the IES and 15% for the avoidance subscale. 7 In a sample of people with SCI, Radnitz et al 30 found that 28% of their sample displayed high scores on at least two of the three characteristic symptoms of PTSD as measured on the IES (re-experiencing the trauma, avoiding trauma related stimuli and persistent increased arousal) and that 12% met the more stringent diagnostic criteria for both the SCID and CAPS. In the present sample 20% reached the cut-o on the intrusion scale and 22.4% reached the cut-o on the avoidance scale, with 14% being above the cuto for both.…”
Section: Discussionmentioning
confidence: 99%